Application of team-based learning to ophthalmology in China - Wu, Wenyi; Pu, Li; Zhang, Endong; Xiong, Siqi; Zhou, Xiaolai; Xia, Xiaobo; Wen, Dan (Frontiers in Public Health, 2022)
OBJECTIVES: The purpose of this study was to explore whether Team Based Learning (TBL) was effective method compared with Traditional Didactic Lecture (TDL) in improving problem solving and study ability about clinical course of ophthalmology in medical students. We also cared about the view and satisfaction of TBL in Chinese students. METHODS: Two hundred and seventy-five students of 5-year clinical medicine program from Central South of China University participated in our study program, one hundred and forty enrolled in modified TBL course. A questionnaire including closed and open-ended items, was distributed to students immediately following completion of the TBL session and we collect one hundred and eight valid questionnaires. Descriptive statistics were used to analyze the quantitative data. The effects of the TBL module on student performance were measured between the groups using a one-way between groups Analysis of Variance (ANOVA) test by the Individual Readiness Assurance Test (IRAT), the Group Readiness Assurance Test (GRAT), and final examination scores (FESs) compared with other class which didn’t apply TBL session. RESULTS: 140 students achieved 72.65 mean test scores on test questions that assessed their knowledge of ophthalmology using the modified TBL strategy compared 135 students achieve 70.8 mean scores with TDL method (p=0.3434). The performance was significantly better during GRAT compared to IRAT in pre-class quiz. TBL learning method was favored and acceptable by most medical students compared to the TDL session. CONCLUSIONS: Application of modified TBL to ophthalmology improved students’ performance, self-study, teamwork and increased their class engagement and satisfaction. But TBL should be further optimized and developed to enhance the educational outcomes.